2019
DOI: 10.1093/biolinnean/blz122
|View full text |Cite
|
Sign up to set email alerts
|

Sex-biased dispersal patterns of a social passerine: complementary approaches and evidence for a role of spatial scale

Abstract: Animal dispersal patterns have important implications for many biological processes, but the measurement of dispersal is challenging and often requires the use of complementary approaches. In this study, we investigated the local-scale sex-biased dispersal pattern in a social bird, the black-throated tit (Aegithalos concinnus), in central China. Spatial genetic autocorrelation analyses suggested that significant fine-scale genetic structure existed in males but not in females. Mark–recapture analyses of ringed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 82 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…This pattern was mainly driven by non-random dispersal-as suggested by both the genetic and the capture-mark-recapture data-associated with environmental heterogeneity within the woodland. Previous studies already showed that capture-mark-recapture data provide accurate information on recent levels of gene flow among bird populations [16,18,30,[66][67][68]; but see [69]. Widespread highly mobile species are likely to experience several environmental conditions and geographical barriers, and thus, they are expected to experience genetic population structure at large geographical scales [70][71][72][73], often following an isolation-by-distance pattern (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was mainly driven by non-random dispersal-as suggested by both the genetic and the capture-mark-recapture data-associated with environmental heterogeneity within the woodland. Previous studies already showed that capture-mark-recapture data provide accurate information on recent levels of gene flow among bird populations [16,18,30,[66][67][68]; but see [69]. Widespread highly mobile species are likely to experience several environmental conditions and geographical barriers, and thus, they are expected to experience genetic population structure at large geographical scales [70][71][72][73], often following an isolation-by-distance pattern (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…2018, Li et al . 2019); in others, they did not match (Robinson & Jones 2014), were not compared (e.g. Carey et al .…”
Section: Literature Reviewmentioning
confidence: 99%